The Effect of Organic Materials on the Acidity and Organic Carbon for Floating Media in Lebak Swampland - Suriadi, Suriadi; Yusran, Fadly H; Fithria, Abdi; Fauzana, Noor Arida; Noor, Ihsan (Technium Sustainability, 2024)
The potential of floating cultivation in lebak swampland, particularly during flood periods, is underscored by this study. Composted aquatic weeds, a rich source of organic matter, are a key component of this potential. The study measures the nutrient content in the compost and chicken manure and analyzes the effect of both on the nutrient content in floating systems. The compost and chicken manure, with their slightly acidic pH and very high organic-C content, hold significant promise. The best-growing medium, a blend of compost (375 g) and chicken manure (375 g), demonstrates optimal pH and organic-C content. Soil treatment (500 g) and compost (250 g) show the most significant effect on eggplant plant height, while the best yield is obtained from the treatment of compost (375 g) and chicken manure (375 g).